The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0088703
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ Receptor-Mediated Inflammation Inhibits Axon Regeneration

Abstract: Anti-glycan/ganglioside antibodies are the most common immune effectors found in patients with Guillain-Barré Syndrome, which is a peripheral autoimmune neuropathy. We previously reported that disease-relevant anti-glycan autoantibodies inhibited axon regeneration, which echo the clinical association of these antibodies and poor recovery in Guillain-Barré Syndrome. However, the specific molecular and cellular elements involved in this antibody-mediated inhibition of axon regeneration are not previously defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 48 publications
6
30
0
Order By: Relevance
“…These studies provide further experimental evidence of the role of macrophages and activating FcγRs mediated-inflammation in Ab-mediated experimental models of autoimmune neuropathies. In line with these animal studies, we also found that macrophages and Schwann cells do express FcγR common chain in the nerves of patients with axonal GBS [43]. The FcγR common chain expression was significantly upregulated in GBS nerves compared to controls and activated macrophages expressing activating FcγRs were found adjacent to widened nodes in axonal GBS patient nerves (Figure 1).…”
Section: Journal Of Clinical and Cellular Immunologysupporting
confidence: 83%
See 2 more Smart Citations
“…These studies provide further experimental evidence of the role of macrophages and activating FcγRs mediated-inflammation in Ab-mediated experimental models of autoimmune neuropathies. In line with these animal studies, we also found that macrophages and Schwann cells do express FcγR common chain in the nerves of patients with axonal GBS [43]. The FcγR common chain expression was significantly upregulated in GBS nerves compared to controls and activated macrophages expressing activating FcγRs were found adjacent to widened nodes in axonal GBS patient nerves (Figure 1).…”
Section: Journal Of Clinical and Cellular Immunologysupporting
confidence: 83%
“…Our studies in op/op mice confirmed the involvement of macrophages in AGA-mediated pathological effects in this model [43]. In order to dissect the contribution of FcγRs-bearing circulating macrophage and FcγRs-expressing resident endoneurial glial cells, a nerve grafting study, in which wild type (WT) or activating FcγRs-null (Fcer1g-/-) nerve segments (donors) were transplanted in background matched WT or Fcer1g-/-(hosts) mice, was carried out [43]. We found that there is significantly more axon regeneration in WT or FcγRs-null grafts implanted in FcγRs-null hosts, compared to WT or FcγRs-null grafts implanted in WT hosts.…”
Section: Journal Of Clinical and Cellular Immunologysupporting
confidence: 82%
See 1 more Smart Citation
“…This observation may therefore relate to the potent immune stimulating activity of mAb targeting TNF receptor super family members such as CD40 and DR4/5 (12)(13)(14)50). In contrast to direct targeting mAb such as rituximab, which are impaired by mFcgRII and hFcgRIIB, these receptors are now known to be an important component of immunomodulatory mAb activity, where they serve to further cross-link the target receptor for optimal signaling (20)(21)(22)(23)(24)(25)reviewed in Ref. 26).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous mFcgRIV +/2 mice, from the European Conditional Mouse Mutagenesis Program consortia distributed by the Helmholtz Zentrum M€ unchen (Munich, Germany), have been described previously (23) and were intercrossed to obtain mFcgRIV 2/2 . All strains were backcrossed onto the BALB/c or C57BL/6J background for at least 10 generations.…”
Section: Animals and Cellsmentioning
confidence: 99%